Medical imaging in clinical trials - Krasnow, Joel; Schwartz, Lawrence H.; Miller, Colin G. (Springer London, 2014)
Medical Imaging in Clinical Trials is a key text in understanding the methodology and the metrics that are required in the field of medical imaging. As the pharmaceutical, biotech and medical device industries continue to identify ways to improve and speed up product development, medical imaging plays a more significant role. Medical Imaging in Clinical Trials aims to educate and provide a hands-on text for those involved in clinical trials and either new to medical imaging and having to assimilate it into clinical trials or requiring to understand the key differences between clinical trial imaging and "routine" clinical imaging.  It is targeted to those professionals involved in clinical trials at the clinical research site, pharmaceutical and medical device industries, and regulators.  This is not the "how to image" book written for the radiologist or Radiological Technologist, but covers the critical aspects of clinical trial methodology that are important for these individuals to understand. This book addresses the ethics and radiation dosages of the different modalities, the end points commonly used for the different trial phases, the acquisition and analysis techniques, as well as the logistics management of medical imaging and the role of the central imaging lab or imaging core lab (ICL) which is now the standard requirement for clinical trials.  Furthermore this text delves into the details of the major therapeutic areas where medical imaging plays a primary or secondary efficacy or safety end point.